GREGORIO JOSÉ RAMÍREZ, THE COLONIAL COSTA RICA’S MERCHANT FLEE, AND INDEPENDENCE - Molina Jiménez, Iván (2021)
This paper examines one of the “founding” fathers of Costa Rica during the independence period: Gregorio José Ramírez. First, it explores Ramírez’s family ancestors at the end of the colonial period; then, it studies merchants from the Central Valley and how they built a political and economic strategically merchant flee; third, it identifies how Ramírez, even though his health issues and limited sources, socially moved to become co-owner of a ship. Finally, this essay explains the way Ramírez gained political capital that allowed him to get a local position from which he played a decisive role during the first years of the Costa Rican State building process.